C. S. Lewis’ mythopoeia of heaven and earth: implications for the ethical and spiritual formation of multicultural young learners - Lee, Seung Chun (Routledge, 2015)
This paper examines C. S. Lewis’ perspective of myth or fantasy literature which has mesmerized, and exerted great impact on, young learners’ hearts. In a society entrenched in postmodern ideologies, the understanding of what principles govern the construction of ethical and spiritual identity of young learners is often lost. In this context, well-written children’s literature can be a wonderful avenue where they can restore the value of the ordinary world, escape from the bondage of sinister world and enhance their sense of supernatural world. This paper argues that these are the major values Lewis held dear in the work of mythopoeia such as The Chronicles of Narnia. It also argues that Lewis’ fantasy novels for children were primarily his attempt to allow them to experience the mythic quality of good stories, i.e., to savour a more ultimate reality and divine truth through the myriad fantastic images and supernatural imagination.